Decision support for men with prostate cancer: Concordance between treatment choice and tumor risk. Issue 2 (29th October 2020) - Filson, Christopher P.; Hong, Fangxin; Xiong, Niya; Pozzar, Rachel; Halpenny, Barbara; Berry, Donna L.
Abstract : Background: Decision support tools improve decisional conflict and elicit patient preferences related to prostate cancer treatment. It was hypothesized that men using the Personal Patient Profile–Prostate (P3P) would be more likely to pursue guideline‐concordant treatment. Methods: Men from a trial assessing the P3P decision support intervention were identified. The primary exposure was allocation to P3P (vs usual care), and the outcome was appropriate treatment per guidelines (eg, low risk = active surveillance). It was assessed whether providers recommended against any treatment options (ie, restricted). A multivariable model was fit for men with low‐risk cancer that estimated the odds of the outcome of interest. Results: This study identified 295 men in the cohort: 113 (38%) had low‐risk disease, 119 (40%) had favorable intermediate‐risk disease, and 63 (21%) had unfavorable intermediate‐risk disease. Among low‐risk patients, more men pursued active surveillance after using P3P whether they were given unrestricted (62% vs 54% with usual care; P = .54) or restricted options (71% vs 59% with usual care; P = .34). After adjustments, only Black race (odds ratio [OR], 0.31; 95% CI, 0.11‐0.89) and restricted options (OR, 0.23; 95% CI, 0.08‐0.65) had an inverse association with the receipt of surveillance for patients with low‐risk prostate cancer. An impact associated with P3P versus usual care (OR, 0.89; 95% CI, 0.36‐2.20) was not observed. Conclusions: Among men in a trial assessing a decision support tool, Black race and restricted treatment options were associated with less use of active surveillance for low‐risk prostate cancer. Although the P3P instrument ameliorates decisional conflict, its use was not associated with more appropriate alignment of treatment with disease risk. Abstract : Among men with low‐risk prostate cancer enrolled in a trial evaluating a decision support intervention, Black men and those with restricted options were less likely to pursue active surveillance. Allocation to the decision support intervention was not associated with increased receipt of risk‐aligned management for patients with prostate cancer.